Operational Risk Management in Indian Banks: Evaluation of Applicability of the RCSA Method Under Advanced Measurement Approach - Mehra, Yogieta S. (Indian Journal of Finance, 2010)
Operational loss events have become the major cause of spectacular business failures (for example, Societe Generale, Madoff, Morgan Stanley amongst others). The trend towards greater dependence on technology, more intensive competition, and globalization have left the corporate world more exposed to operational risk than ever before. The paper explores the feasibility of implementation of RCSA as an Operational risk management method when Indian banks migrate to Advanced Measurement Approach (for calculating operational risk capital charge). RBI has declared the time schedule for implementation of AMA by Indian Banks and many large banks aim to file their application by April 2012. A study of Annual reports of 31 banks followed by survey of 900 employees of these 31 banks indicates insufficient awareness about operational risk, lack of discipline in organizing and attending workshops and high attrition rate in some categories of banks. These would be impediments if banks desire to follow RCSA method in implementing the advanced measurement approach by April 2012. The study underscores the need to revamp many traditional practices of banks in order to be prepared for the competitive globalised banking environment where many large banks have started following Advanced Measurement Approach to efficiently manage operational risk.